2018
DOI: 10.1101/334169
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-outbreak of ST37 and a novel ST3006 Klebsiella pneumoniae from multi-site infection in a neonatal intensive care unit: a retrospective study

Abstract: 21 sequencing; Neonatal intensive care unit 22 23 2 Summary 24 Background: The spread of carbapenem resistance among Klebsiella pneumoniae (K. 25 pneumoniae) is a major public health problem, particularly in neonatal intensive care 26 units (NICUs).27Aim: To describe the nosocomial co-outbreak of ST37 and a new sequence type 28 ST3006 K. pneumoniae, causing catheter-related bloodstream infections in NICU. 29Methods: Fifteen strains of K. pneumoniae were isolated from seven neonates during 30 June 3-28, 2013, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The clustered occurrence of some Klebsiella pneumoniae ( Kp ) strains suggests possible outbreaks and may provide clues about infection sources in this study. Strains ST35 and ST37, which were responsible for more than half of all GNB sepsis in this study, have been associated with MDR and reported to be sources of outbreaks within NICU settings outside sSA [ 59 61 ]. Both ST35 and ST37 have also been detected in the feces of healthy adults and animals in the community [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clustered occurrence of some Klebsiella pneumoniae ( Kp ) strains suggests possible outbreaks and may provide clues about infection sources in this study. Strains ST35 and ST37, which were responsible for more than half of all GNB sepsis in this study, have been associated with MDR and reported to be sources of outbreaks within NICU settings outside sSA [ 59 61 ]. Both ST35 and ST37 have also been detected in the feces of healthy adults and animals in the community [ 62 ].…”
Section: Discussionmentioning
confidence: 99%